INDUSTRY 5.0: DIGITALIZATION OF ACCOUNTING THROUGH THE EMERGENCE OF E-INVOICE - GORE BEATRICE ELENA; SCHITZ CORNELIA-ANA; RADU FLORIN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
Industry 5.0 is defined by the connection between technology and human skills, enhancing the field of accounting through the integration of artificial intelligence (AI), automation, and advanced data analytics solutions. In this new industrial stage, the focus is not only on automation but also on supporting human activity through the personalization of processes and technology [14]. In this context, accounting professionals are challenged to expand their traditional roles, becoming involved in predictive analysis, strategic advisory, and risk assessment, supported by digital tools. A core element of Industry 5.0 in accounting is the use of AI to simplify complex operations. Through these technologies, financial data is processed quickly, enabling anomaly detection and improving the accuracy of reports[8]. For automating routine tasks, robots and software are used, such as account reconciliation, invoice management, and transaction auditing, freeing up human resources for higher-value activities. In this way, AI helps increase efficiency and reduce errors in accounting processes [10]. The collaboration between humans and machines, characteristic of Industry 5.0, opens new perspectives for accounting, supporting in-depth analysis and decision-making based on precise information. Accountants can use advanced digital platforms to assess risks, optimize cost structures, and anticipate market fluctuations, relying on data and advanced analytical models [6].